1999
DOI: 10.1046/j.1440-1614.1999.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Posttraumatic Stress Disorder on Partners and Children of Australian Vietnam Veterans

Abstract: These findings support overseas studies that indicate that the families of PTSD sufferers are also impacted by the disorder. In this study, the families of Australian Vietnam veterans experienced more conflict and their partners were significantly more psychologically distressed (i.e. somatic symptoms, anxiety, insomnia, social dysfunction, depression and low self-esteem) than a matched control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 14 publications
3
108
2
4
Order By: Relevance
“…Compared to the partners of non-veterans, the partners of Australian Vietnam veterans with PTSD reported higher levels of somatic complaints, depression, anxiety, insomnia, social difficulties, and family conflict, and lower levels of self-esteem, family cohesion, and family expressiveness (Westerink and Giarratano 1999). In a similar study, spouses of Australian Vietnam veterans were more likely to report depression if the veteran had PTSD (O'Toole et al 2010).…”
Section: Domestic Violencementioning
confidence: 85%
See 1 more Smart Citation
“…Compared to the partners of non-veterans, the partners of Australian Vietnam veterans with PTSD reported higher levels of somatic complaints, depression, anxiety, insomnia, social difficulties, and family conflict, and lower levels of self-esteem, family cohesion, and family expressiveness (Westerink and Giarratano 1999). In a similar study, spouses of Australian Vietnam veterans were more likely to report depression if the veteran had PTSD (O'Toole et al 2010).…”
Section: Domestic Violencementioning
confidence: 85%
“…Later studies of children of Vietnam veterans with PTSD showed elevated levels of psychopathology on MMPI and MMPI-II scales and elevated hostility compared to population norms (Beckham et al 1997). In Australia, children of Vietnam veterans with PTSD reported higher levels of family conflict, but not psychological distress, when compared to children of non-veterans in terms of psychological distress or self-esteem (Westerink and Giarratano 1999). Another study of children of Australian Vietnam veterans with PTSD reported poor family problemsolving and poor family affective responsiveness, but not selfesteem, PTSD symptomatology, or other measures of family functioning, compared to children of veterans without PTSD or children of non-veterans (Davidson and Mellor 2001).…”
Section: Child Healthmentioning
confidence: 98%
“…Although these studies are consistent with our failure to find a link between paternal PTSD and PTSD in Holocaust offspring, these studies differ because the other parent was not specifically exposed to trauma. Although PTSD in combat veterans has been known to affect spouses as well as offspring (Dekel & Solomon, 2006;Franciskovic et al, 2007), it has also been proposed that the effect of paternal combat PTSD on offspring may be partially buffered by non-affected wives of these veterans (Westerink & Giarratano, 1999). Yet, the contribution of maternal trauma or PTSD in such studies has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Children of veterans according to these studies reported higher levels of conflict in their families but no significant differences on measures of psychological distress from control groups (Westerink and Giarratano 1999). Findings from Ruscio, Weathers, King, and King (2002) showed that emotional numbing was the only aspect of PTSD uniquely associated with veterans' perceived relationships with their children.…”
Section: Discussionmentioning
confidence: 83%